2003
DOI: 10.6090/jarq.37.105
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in N2 Fixation Activity and N Enrichment in Paddy Soils as Affected by Soil Management in the Northern Area of Japan

Abstract: Enhancing the indigenous ability of biological N 2 fixation (BNF) in paddy soils to increase N fertility is important to develop sustainable rice cultivation systems. This study aimed at evaluating the effect of light conditions and long-term soil management on the seasonal changes in the BNF activity of paddy soils associated with the decomposition of rice straw and cellulose, by determining the acetylene reduction activity (ARA) and N enrichment in the Tohoku region of Japan under cool temperate conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…The positive relation of 15 N 2 fixation with the total-C and mineralizable-N contents under the light conditions indicated the importance of the role of decomposable organic matter in the increase of the populations of phototrophic N 2 fixers. Among the organic materials, fresh organic materials such as manure and rice straw were found to be more effective in enhancing 15 N 2 fixation than the compost, which is in agreement with the trends in N enrichment in field evaluation 9 . On the other hand, soils with lower total-C and mineralizable-N contents tended to depend more on heterotrophic BNF, presumably due to the alleviation of the adverse effect of NH 4 on heterotrophic N 2 fixation in part 11 .…”
Section: Effect Of Soil Managementsupporting
confidence: 74%
See 3 more Smart Citations
“…The positive relation of 15 N 2 fixation with the total-C and mineralizable-N contents under the light conditions indicated the importance of the role of decomposable organic matter in the increase of the populations of phototrophic N 2 fixers. Among the organic materials, fresh organic materials such as manure and rice straw were found to be more effective in enhancing 15 N 2 fixation than the compost, which is in agreement with the trends in N enrichment in field evaluation 9 . On the other hand, soils with lower total-C and mineralizable-N contents tended to depend more on heterotrophic BNF, presumably due to the alleviation of the adverse effect of NH 4 on heterotrophic N 2 fixation in part 11 .…”
Section: Effect Of Soil Managementsupporting
confidence: 74%
“…The details of soil management of the field trials were reported elsewhere 9 . The properties of the soils are presented in Table 1.…”
Section: Soil Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the effect of returning the soil surface to its initial condition might be beneficial for biological nitrogen fixation by algae which proliferate on the puddled soil surface (Roger and Kulasooriya 1980). Kondo and Yasuda (2003) reported that the amount of biologically fixed nitrogen would be 1.6-2.0 g m À2 in one cropping season for paddy fields in Japan under conventional management. Moreover, total N in the soil surface layer significantly increased compared with conventional water treatment when an early drained condition was introduced to a clayey paddy field, and algae proliferation was suggested on such a drained moist soil surface (Kobayashi et al 2000).…”
Section: Weeding and Soil Churningmentioning
confidence: 99%